Rates of return to degrees across British regions - Nigel C. O'Leary; Peter J. Sloane (Institute for the Study of Labor (IZA), 2006)
Earlier papers have found considerable heterogeneity in the returns to degrees in relation to subjects of study, degree classification and higher education institution. In this paper we examine heterogeneity of returns across British regions using the Labour Force Survey. We find substantial variations in the financial rewards available to graduates across regions with much higher returns in London and the South East than elsewhere, although adjusting for regional differences in the cost-of-living narrows such differences considerably. Decompositional analysis, after controlling for regional differences in both occupational and industrial structures, suggests that coefficient effects dominate composition effects, consistent with agglomeration effects being important. These results have implications for the recent changes to student funding in England, Scotland and Wales.
Keywords: A22; A23; I21; J31; R1; 330; education; degree; rates of return; regions